Review: Ethno-zoological study of animals-based medicine used by traditional healers of North-east India (Asian Journal of Ethnobiology, 2021)
Abstract. Hussain JF, Tynsong H. 2020. Review: Ethno-zoological study of animals-based medicine used by traditional healers of Northeast India. Asian J Ethnobiol 4: 1-22. For ages, plants and animals have been used in human cultures as therapeutics. Animals have not only acted as a source of food for humans but have also been commonly used in applications such as medicine, clothes, and other related services. The use of animals and animal products in traditional methods of treating diseases, and for many different reasons, dates back to the early days of civilization. Treatment of human diseases using animal-derived products is called zootherapy or ethno-zoology. Despite the worldwide utilization of ethno-zoology in the form of traditional medicines based on animals, a thorough study of zootherapy in comparison to plant-based medicinal research is still ignored. This study highlights available knowledge on ethno-zoological therapeutic applications used by different traditional healers of North-East (NE) India. Concerning the frequency of animal species, the use of mammals and mammalian products is the highest in NE India compared to other animal groups. In contrast, the use of fish-based medicine in the state of Manipur is prevalent compared to other animal species. In Arunachal Pradesh, the use of insects is high in traditional medicines.
Keywords: Animals-based medicines, Ethno-zoology, North-East India, Traditional knowledge.